Implications of Low Student Enrollment for Physical Education Practices in Rural Elementary Schools - Jajang dede Mulyani; Aisyah Apriliciciliana Aryani; Kuat Leksono (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2026)
This study analyzes how low student numbers in rural elementary schools affect the implementation of physical education (PE). The research aims to identify the pedagogical, organizational, and contextual challenges faced when class sizes fall far below the national standard. Using a qualitative descriptive design, data were collected through semi-structured interviews with principals, physical education teachers, classroom teachers, and selected students, as well as classroom observations and document analysis in six rural elementary schools in Banyumas Regency, Central Java. The findings indicate three main implications. First, although smaller classes allow more individualized instruction, teachers struggle to create dynamic learning environments due to limited peer interaction, reduced group activities, and low competitive engagement. Second, minimal enrollment leads to structural constraints such as limited facilities, inadequate equipment, and reduced institutional support, which directly affect instructional quality. Third, demographic decline and community attitudes toward rural schooling further reduce student participation and threaten program sustainability. The study concludes that rural schools require targeted policy support, adequate resource allocation, and adaptive instructional strategies to sustain meaningful PE learning. Strengthening community involvement and adopting flexible activity-based models are recommended to support holistic student development in rural contexts.